ANALISIS KELEMBAGAAN ORGANISASI DI BADAN PENANGGULANGAN BENCANA DAERAH PROVINSI JAWA TENGAH - Rezha Mehdi Bazargan; Sri Suwitri; Maesaroh Maesaroh (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
The organizational structure is a hierarchical arrangement of organizations ranging from the lower level to the upper level. In each hierarchical division of labor are complex and require specialized expertise in each task execution. BPBDs structure Central Java province has advantages in the job descriptions of the structure of the organization. Human resources have yet to be appropriate competencies for the organization's needs, the emergence of a dispute between the employees and the workload between field uneven. Results of the study aims to describe and analyze the institutional organization and organizational design BPBDs Central Java Province. This type of research used qualitative descriptive data analysis using taxonomic analysis techniques. Selection informant by purposive sampling that later developed through snowball sampling. Data collection techniques used were observation, interviews, documentation and literature. Based on this research, organizational strategy realized in accordance with the target effectively and efficiently manage resources. BPBDs Central Java province has a flat organizational structure, with the advantages of the structure of the job descriptions. Extensive networks reflected on the steering element. Functional organization has not materialized yet being filled with functional groups. As a learning organization, BPBDs Central Java Province continues to improve the quality of employees and freedom emergence of collective aspirations. In terms of organizational design, structural configurations according to the Regional Disaster Management Agency of Central Java province is a simple structure and the structure of professional bureaucracy. Institutional organization BPBDs Central Java Province is still in institutional strengthening. Expected to BPBDs Central Java province to do to optimize the budget to improve the competence of personnel resources and infrastructure, consider filling the functional position, and initiate meetings on the middle line, in order to create a pattern of horizontal communication with the operating core.